An exploration of how working in the Improving Access to Psychological Therapies (IAPT) programme might affect the personal and professional development of counsellors: an analytical autoethnographic study. Issue 6 (2nd November 2018) - Mason, Richard; Reeves, Andrew
ABSTRACT: Since implementing the Improving Access to Psychological Therapies (IAPT) programme in 2008, provision of counselling and other idiographic approaches to psychological therapy in the English National Health Service (NHS) has been reduced to several manualised therapies supported by National Institute of Health and Care Excellence (NICE) guidelines for depression and anxiety. Many counsellors who previously provided psychological therapies in the NHS subsequently left or retrained in IAPT compliant models of treatment. This study explores the effect that working in IAPT services over an eight-year period had on the professional and personal development of the primary author, resulting in a strong exhortation for counsellors to take advantage of, and influence the professional development opportunities it presents. This study takes an analytical autoethnographic approach, undertaking the thematic analysis of naturally occurring data, taken from previously published opinion columns in a professional journal, and an unpublished doctoral assignment to illuminate previously unrecognised narrative. Themes of ideological resistance, and being out-group resulting in a sense of professional loss, uncertainty and cessation of professional development preceded acceptance of the IAPT nomothetic ideology. After which, a sense of being in-group facilitated a sense of gain, certainty, and the re-implementation of professional growth. Counsellors in IAPT may be prejudiced by their idiographic ideology. Professional uncertainty and a sense of loss could inhibit professional development. Development of a pluralistic ideological stance, and integrative approach to treatment is encouraged. Counsellors who accept a Cinderella like status in IAPT, are exhorted to adapt, influence from within, and thrive in IAPT.